The impact of macroprudential housing finance tools in canada - Allen, Jason; Grieder, Timothy; Peterson, Brian; Roberts, Tom (Journal of Financial Intermediation, 2020)
This paper combines loan-level administrative data with household-level survey data to analyze the impact of recent macroprudential policy changes in Canada using a microsimulation model of mortgage demand of first-time homebuyers. Policies targeting the loan-to-value ratio are found to have a larger impact on demand than policies targeting the debt-service ratio, such as amortization. In addition, we show that loan-to-value policies have a larger role to play in reducing default than income-based policies.